The Relationship between Clean and Healthy Living Behavior and the Incidence of Pityriasis Versicolor in Ambon City Orphanages - Wattimury, Marcelino; Manuputty, Amanda Gracia; Hursepuny, Valentine (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Pityriasis versicolor is a cosmopolitan fungal infection in tropical areas. The revalence is 50%, and it ranks second among Indonesia's most common skin diseases. Pityriasis versicolor was one of the ten worst skin diseases in Maluku Province. It was caused by environmental, behavioral, and public awareness issues, like people who don't follow clean and healthy living habits (CHLB). Purpose: This study aims to determine the relationship between clean and healthy living behaviors and pityriasis versicolor incidence in Ambon City orphanage children in 2024. Methods: This study is conducted by using quantitative research with observational analytical studies through a cross-sectional approach. The sample was taken using total sampling criteria, where population members who met the criteria would be used as a sample. Subsequently, sample of 32 respondents was obtained in this study (84%). Result: The analysis showed that the CHLB level was poor in 22 people (57.9%), and the proportion of pityriasis versicolor incidence was 32 (84.2%). Bivariate analysis showed the significance of the relationship between CHLB and the incidence of pityriasis versicolor with p-value = 0.003. Conclusion: It can be concluded that there is a significant relationship between clean and healthy living behavior and the incidence of pityriasis versicolor in orphanage children in Ambon City. Therefore, it is important to raise awareness about clean and healthy living practices to reduce the incidence of pityriasis versicolor.